Migration, stereotypes and prejudices yesterday and today: the Italian case. - Olivieri, Mabel (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2016)
This article describes and documents the prejudices and the stereotypes applied to the Italian emigrants during the last and the present century, not only in the receiving countries but also in Italy itself from other italians (politicians, men of letter, professionals) whose national pride was hurted by the shame of the Italian communities abroad: it draws a comparison between the stereotypes against European emigrants and those that today fall on the foreign immigrants in Europe; it underlines the role played in these events by both nationalisms, from the expelling and receiving countries.